Modulation of the Intratumoral Immune Landscape by Oncolytic Herpes Simplex Virus Virotherapy - Yin, Jie; Markert, James M.; Leavenworth, Jianmei W. (Frontiers in Oncology, 2017)
Vaccines and immunotherapeutic approaches to cancers with the advent of immune checkpoint inhibitors and chimeric antigen receptor (CAR)-modified T cells have recently demonstrated preclinical success and entered clinical trials. Despite advances in these approaches and combinatorial therapeutic regimens, depending on the nature of the cancer and the immune and metabolic landscape within the tumor microenvironment, current immunotherapeutic modalities remain inadequate. Recent clinical trials have demonstrated clear evidence of significant, and sometimes dramatic, antitumor activity and long-term survival effects of a variety of oncolytic viruses (OVs), particularly oncolytic herpes simplex virus (oHSV). Acting as a multifaceted gene therapy vector and potential adjuvant-like regimens, oHSV can carry genes encoding immunostimulatory molecules in its genome. The oncolytic effect of oHSV and the inflammatory response that the virus stimulates provide a one-two punch at attacking tumors. However, mechanisms underlying oHSV-induced restoration of intratumoral immunosuppression demand extensive research in order to further improve its therapeutic efficacy. In this review, we discuss the current OV-based therapy, with a focus on the unique aspects of oHSV-initiated anti-viral and antitumor immune responses, arising from virus-mediated immunological cell death to intratumoral innate and adaptive immunity.